ANALISIS PEMASARAN OTAK-OTAK IKAN "SELARAS LEGENDARIS" DI KOTA BANDUNG - -, junianto (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2024)
Marketing strategy is a way to achieve marketing goals, involving target markets, product positioning, marketing mix and budget. In business, marketing strategies are very important to survive in a competitive market. This research aims to identify the added value of processing mackerel fish into otak-otak, namely the "Otak-Otak Selaras Legendaris" in Cicendo District, Bandung City, as well as to analyze the market. The method used in this research is the case study method.  The data used in this research is primary data. Data collection in this research includes observation, interviews and logging. The data analysis used in this research is a qualitative descriptive analysis method. Based on the results of the analysis that has been carried out regarding the opportunities, threats, strengths and weaknesses of the Otak-Otak Selaras Legendaris Ikan Tenggiri, the results show that this business has great opportunities because the demand and need for ready-to-eat food is high in the current era. Processing mackerel fish otak-otak produces significant economic benefits. The processing of mackerel fish into otak-otak is clear evidence of how the fisheries sector can increase added value through innovation and efficiency. So with this opportunity, improving product quality and service quality will maintain customer loyalty.